Audiovisual Platforms and Higher Education: Integration and Media Empowerment - Beltrán, Ana María; Maldonado, Juan Carlos; Buitrago, Alex (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
This study analyzes media empowerment in higher education in Ecuador, focusing on the impact of platforms like Instagram and YouTube on Generation Z's learning. Using a mixed-methods approach, the role of edutubers and edugrammers in media competencies and autonomous learning was assessed. A qualitative survey was conducted with 300 students and 50 teachers, along with an examination of 50 educational materials on these platforms and structured interviews. The results indicate that these platforms promote interactive and collaborative learning, although challenges such as technological access inequality and the need for teacher training are highlighted. With proper support, these tools can transform education and prepare young people for the digital environment.